Pengaruh Pemberian Antibiotika Profilaksis Golongan Penisilin dengan Golongan Sefalosporin terhadap Tanda Klinis IDO Superfisial dan LOS ada Pasien SC di Rumah Sakit “X” - Teulis Sumiartini; Dian Ratih Laksmitawati; Hesti Utami Ramadaniati; Ranald Irwanto (JURNAL ILMU KEFARMASIAN INDONESIA, 2021)
A hospital "X" in Jakarta has priority obstetrics services with a high birth rate. Sectio caesarea (SC) at the hospital uses prophylactic antibiotics penicillin and cephalosporins to reducing superficial Surgical Site Infection (IDO). Complication of infection can increase prolongs stay patient (length of stay - LOS). The aim of this study is to look the influence administration of penicillin prophylactic antibiotics with cephalosporins towards the clinical signs of superficial IDO and LOS to SC patients in hospital "X". The test sample calculated using a formula of two proportions difference with retrospective data tracing from medical records which are analyzed using the Chi-Square method with the help of Microsoft Excel to determine the influence administration of penicillin prophylactic antibiotics with cephalosporins towards the clinical signs of superficial IDO and LOS. The results showed that the chi-square calculated value in bivariate analysis of prophylactic antibiotics with LOS and clinical signs of IDO are smaller than the Chi-Square table value (Chi-Square table value at degree of freedom (DF) 1 and significance of 0.05 = 3.8415) with a p value greater than 0.05. In conclusion, there is no statistically significant difference in influence between the group receiving penicillin prophylactic antibiotics with the group receiving cephalosporin prophylactic antibiotics towards the clinical signs of superficial IDO and LOS to SC patients in hospital "X".